2019
DOI: 10.24272/j.issn.2095-8137.2019.039
|View full text |Cite
|
Sign up to set email alerts
|

High egg rejection rate in a Chinese population of grey-backed thrush (Turdus hortulorum)

Abstract: Reflectance of thrush eggs was averaged from three eggs from the nest in Figure 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Our results show that the Chestnut Thrush has a moderate egg rejection ability, which is similar to results from European studies of the Song Thrush and the Blackbird (Grim and Honza 2001). Conversely, we show that the Chinese Thrush has a strong egg recognition ability, which is similar to that of the Spanish Blackbird (Soler et al 2015;Ruiz-Raya et al 2016) and the Grey-backed Thrush in eastern China (Yang et al 2019b;Zhang et al 2019). Many potential hosts, even if not parasitized currently, may have retained an ability to reject eggs from a history with the parasite (Peer and Sealy 2004).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Our results show that the Chestnut Thrush has a moderate egg rejection ability, which is similar to results from European studies of the Song Thrush and the Blackbird (Grim and Honza 2001). Conversely, we show that the Chinese Thrush has a strong egg recognition ability, which is similar to that of the Spanish Blackbird (Soler et al 2015;Ruiz-Raya et al 2016) and the Grey-backed Thrush in eastern China (Yang et al 2019b;Zhang et al 2019). Many potential hosts, even if not parasitized currently, may have retained an ability to reject eggs from a history with the parasite (Peer and Sealy 2004).…”
Section: Discussionmentioning
confidence: 62%
“…Soler et al (2015) found that the rejection rate of Blackbirds was 71.4%. Recent studies in China have even found that the rejection rate of Grey-backed Thrushes (Turdus hortulorum) to foreign eggs is almost 100% (Yang et al 2019b;Zhang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moksnes et al 1991b): if the host did not reject the experimental egg within six days, it was recorded as accepted; if the egg was pecked, disappeared or deserted within six days, it was considered rejected. Experimental nests that were predated or destroyed because of bad weather within six days were not counted in the results of the experiment (see also Yang et al 2019).…”
Section: Egg Recognition Experimentsmentioning
confidence: 99%
“…However, methodologies vary among studies, which may restrict the feasibility for comparisons. For example, combining with those studies that were filtered out from meta-analyses but were related with this topic, inconsistencies were found in the timing of testing, egg types (real or model eggs; Yang et al 2015a ; Peer 2017 ; Yi et al 2020 ), mimetic degree ( Underwood and Sealy 2006 ; Zölei et al 2012 ; Yang et al 2019b ), egg size and materials ( Guigueno and Sealy 2009 ; Roncalli et al 2016 ), egg colors ( Feng et al 2019 ), egg spots or patterns ( Wang et al 2015 ), or 3D or flat objects ( Poláčeket al 2013 ). Furthermore, the shapes and materials used in detecting nest sanitation varied as well.…”
Section: Discussionmentioning
confidence: 99%